Deteriorating agriculture: it’s reasons and impacts on socio-economic profile of J&K state - Malik, Ishfaq Ahmad; Rather, Ajaz Ahmad (Asian Journal of Agriculture and Rural Development, 2018)
In terms of dependence on livelihoods and employment, the state of Jammu and Kashmir can be considered as agrarian, hence the overwhelming majority of the people live in rural areas. There are many reasons that have led to a dwindling share of GDP of the sector at a time when it should have retained its role given large proportion of people depending on it. These include: Reduction in public expenditure in the sector after reforms, decrease in agricultural land due to conversion, lack of appropriate irrigation facilities, and acute lack of infrastructure, lack of quality pesticides, occasional flooding, and lack of research. This imbalance between production and employment has resulted into compromised socio-economic profile of the state which includes: Low per capita income, compromised Food security, large Capital outflow, and Low employment. Therefore, in a bid to arrest any further deterioration in its socioeconomic profile, it is imperative for the state to initiate a stream of measures that will enhance the productivity in the sector and safeguard it from undue competition from abroad.